Turnout-boosting activities as a sign of self-organization of society in Poland and the Czech Republic - Strzemecka, Stella (Journal of Public Governance, 2013)
The paper addresses the role of NGOs in stimulating the need to communicate and collaborate in the Polish social campaign “Masz głos, masz wybór”, and the activity of Czech associations – Změň politiku i Vyměňte polityki. The paper is also an attempt to explain the earlier phenomenon of the election “boom” of Czech citizens.